COINOCULAÇÃO DE Rhizobium tropici COM ESPÉCIES DE Bacillus NA REDUÇÃO DA ADUBAÇÃO FOSFATADA EM FEIJÃO - ANDRADE, Beatriz Pisa; SILVA, Perlla Thais Almeida; SOUZA, Maria Carolina; TEIXEIRA FILHO, Marcelo Carvalho Minhoto; OLIVEIRA, Carlos Eduardo da Silva (ANAIS DO ENIC, 2026)
.